2016
DOI: 10.1167/iovs.16-19305
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Quantification of the Transcorneal Electrical Stimulation (TES)–Induced Protective Effects on N-Methyl-N-Nitrosourea–Treated Retinas

Abstract: METHODS. N-methyl-N-nitrosourea-administered mice received TES or sham stimulations and were subsequently subjected to electroretinography (ERG), multielectrode array (MEA), and histologic and immunohistochemistry examinations. Quantitative reverse transcriptionpolymerase chain reaction (qRT-PCR) analyses were also performed to determine the mRNA levels of Bax, Bcl-2, Calpain-2, Caspase-3, brain-derived neurotrophic factor (BDNF), and ciliary neurotrophic factor (CNTF). RESULTS.Amplitudes of ERG b-wave in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The cone cell is affected later than the rod cell in the model of MNU-induced RP, which is similar to that of human RP [32]. In accordance with other reports [33,34], the reduced amplitude of the cone response in ERG in our study was significantly lower than that of rod response. Thus, the range of change in amplitude of the cone response in ERG on D1 might be too small to demonstrate the Alda-1-induced protection, which was more obvious in rod response.…”
Section: Discussionsupporting
confidence: 91%
“…The cone cell is affected later than the rod cell in the model of MNU-induced RP, which is similar to that of human RP [32]. In accordance with other reports [33,34], the reduced amplitude of the cone response in ERG in our study was significantly lower than that of rod response. Thus, the range of change in amplitude of the cone response in ERG on D1 might be too small to demonstrate the Alda-1-induced protection, which was more obvious in rod response.…”
Section: Discussionsupporting
confidence: 91%
“…Our RCT found central visual improvements in VA and CS following TES, which is supported by a study of TES in mice with an induced form of RP that showed greater preservation of the central than of the peripheral photoreceptors. (Tao et al 2016) Another previous small-scale RCT of TES in RP patients indicated significant preservation of VA but did not measure VFs, (Robles-Camarillo et al 2013) while another group reported a significant improvement in peripheral VF area but not VA;(Schatz et al 2011) therefore, a larger scale RCT conducted over several years including several aspects of visual function and genotyping is needed to elucidate the effects since RP is a heterogeneous disease. The present trial attempted to reduce the risk that chance could have accounted for a significant improvement outside typical test variability for visual function by utilizing a strict criteria of improvement at two consecutive follow-up visits; however, appropriately powered larger scale trials are still needed before these interventions may be recommended clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Previous basic science studies indicate that electro-stimulation most likely does not have a direct effect on photoreceptor cell survival or function, but rather may exert an indirect effect on photoreceptors through its modulation of retinal microglia and secretion of several retinal neurotrophic factors and nerve growth factors from Müller cells, as well as changes in the microenvironment, such as downregulation of cytokines responsible for regulating immune responses (i.e., interleukins), or reductions in gene expression levels for proteins associated with inflammation or apoptosis. (Zhou et al 2012)(Tao et al 2016)(Sehic et al 2016) Previous in vitro studies suggest that electro-stimulation of the retina inhibits microglial activation and their secretion of proinflammatory and toxic cytokines (Schmid et al 2009)(Zhou et al 2012); however, it is also possible that the microglia response in vivo is due to its sensitivity to microenvironment changes rather than to direct effects of electro-stimulation. It has been proposed that the neuroprotection mediated by electrostimulation occurs via several counteracting trophic factors that mediate microglial activation and suppression to create homeostatic balance and a nurturing microenvironment suitable for the rescue of apoptotic photoreceptor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Transcorneal Electrical Stimulation (TES) is a minimally invasive, readily applicable intervention that may have the potential to slow the progression of retinitis pigmentosa (RP) or improve visual function as per findings in animal or in vitro models of RP [1, 2] and human studies [36]. Several previous basic science studies support the hypothesis that TES might induce a beneficial effect via several mechanisms: neurotrophic, anti-apoptotic, anti-glutamate, and anti-inflammatory [1, 2], which are believed to influence visual function improvements and help to reduce the progression rate of RP. It has been proposed that the neuroprotection mediated by electro-stimulation occurs via several counteracting trophic factors that mediate microglial activation and suppression to create homeostatic balance and a nurturing microenvironment suitable for the rescue of apoptotic photoreceptor cells [1, 2].…”
Section: Introductionmentioning
confidence: 99%